Cross‐Linked Poly‐4‐Acrylomorpholine: A Flexible and Reversibly Compressible Aligning Gel for Anisotropic NMR Analysis of Peptides and Small Molecules in Water. Issue 50 (8th November 2021) - Farley, Kathleen A.; Koos, Martin R. M.; Che, Ye; Horst, Reto; Limberakis, Chris; Bellenger, Justin; Lira, Ricardo; Gil‐Silva, Leandro F.; Gil, Roberto R.
Abstract: Determination of the solution conformation of both small organic molecules and peptides in water remains a substantial hurdle in using NMR solution conformations to guide drug design due to the lack of easy to use alignment media. Herein we report the design of a flexible compressible chemically cross‐linked poly‐4‐acrylomorpholine gel that can be used for the alignment of both small molecules and cyclic peptides in water. To test the new gel, residual dipolar couplings (RDCs) and J ‐coupling constants were used in the configurational analysis of strychnine hydrochloride, a molecule that has been studied extensively in organic solvents as well as a small cyclic peptide that is known to form an α‐helix in water. The conformational ensembles for each molecule with the best fit to the data are reported. Identification of minor conformers in water that cannot easily be determined by conventional NOE measurements will facilitate the use of RDC experiments in structure‐based drug design. Abstract : Determination of the solution We synthesized a new anisotropic alignment media, p‐4‐AM, that is compatible with water and reusable. P‐4‐AM was characterized with strychnine hydrochloride as a model compound and used to determine the solution conformation of a cyclic peptide. This alignment media will increase the use of residual dipolar couplings (RDC) in structure‐based drug design by enabling the identification of minor solution conformations in water.